Belajar Bahasa Inggris Dengan Alam Di Desa Mompang - Harahap, Rosni; Siregar, Rini Kesuma; Sibuea, Ernirawati (FORDICATE, 2021)
The essence of learning is an activity carried out by a person to gainknowledge and skills as a provision for the future. Learning with teachers andfriends in class, joking and playing together is a special moment now forstudents after so many months of studying and working from home using theinternet. Therefore, choosing fun English learning activities with nature is theright solution for children in Mompang Village. Learning in nature is done withgroup friends and accompanied by the PKM team. They study outside the room,some study in the village hall yard, in the residents' garden and some even go tostudy behind the residents' houses where the locations are rice fields, gardens,cowsheds and mountains. The method used is direct learning or direct learning.Learn to practice and end by the PKM team. In conclusion, learning Englishwith nature makes it easier for children to understand English. They are veryenthusiastic and eager to learn in nature.